2021
DOI: 10.1093/nar/gkab264
|View full text |Cite
|
Sign up to set email alerts
|

Water structure around a left-handed Z-DNA fragment analyzed by cryo neutron crystallography

Abstract: Even in high-quality X-ray crystal structures of oligonucleotides determined at a resolution of 1 Å or higher, the orientations of first-shell water molecules remain unclear. We used cryo neutron crystallography to gain insight into the H-bonding patterns of water molecules around the left-handed Z-DNA duplex [d(CGCGCG)]2. The neutron density visualized at 1.5 Å resolution for the first time allows us to pinpoint the orientations of most of the water molecules directly contacting the DNA and of many second-she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…S2). This feature had already been correctly predicted in the 1990s (Harper et al, 1998) and was confirmed by the current results, where the predicted hydration sites are in good agreement with the water positions solved by neutron diffraction (PDB entry 7jy2; Harp et al, 2021). Now, with hydration data for both the base and backbone, we observe a spherical water density HS forming a bridge between the N2(G) minor-groove atoms and the OP2 atom of the following phosphate.…”
Section: Tablesupporting
confidence: 89%
“…S2). This feature had already been correctly predicted in the 1990s (Harper et al, 1998) and was confirmed by the current results, where the predicted hydration sites are in good agreement with the water positions solved by neutron diffraction (PDB entry 7jy2; Harp et al, 2021). Now, with hydration data for both the base and backbone, we observe a spherical water density HS forming a bridge between the N2(G) minor-groove atoms and the OP2 atom of the following phosphate.…”
Section: Tablesupporting
confidence: 89%
“…The Z II conformation has not been observed in any Z-RNA molecules of natural sequence [ 9 , 10 ]. The rotation of the GpC phosphate into a Z II conformation, as seen in Z-DNA structures [ 33 ], would bring the OP1 oxygen within ~2.3 Å of guanosine’s 2′OH, and may contribute to unfavorable repulsive forces.…”
Section: Structural Characteristics Of the Z-conformationmentioning
confidence: 99%
“…Theoretical work [ 67 , 68 ], ab initio modeling [ 62 , 63 ], and experimental studies [ 1 , 27 , 28 , 29 , 30 , 31 , 64 , 69 ] all suggest that the physical explanation for this increased stability is due to water-mediated hydrogen bonding networks facilitated by the exocyclic N2 group of guanosine residues, which is absent in adenosine residues. In the Z-conformation, N2 aminos of syn guanine bases form water-mediated hydrogen bond networks involving nearby phosphate groups ( Figure 5 A) [ 10 , 33 ]. Adenine, lacking an N2 amino group, is unable to make the same bridging connection and stabilize the syn conformation as effectively.…”
Section: Formation and Stability Of Z-conformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most theoretical and computational studies are carried out in either a dilute environment or in the absence of water molecules. A recent study demonstrated how water molecules donate or accept hydrogen bonds within prominent parts of the DNA structure, including inside grooves and around the sugar–phosphate backbone [ 126 ]. This opens up new possibilities for studying how molecular crowders affect DNA structure and function with the presence of water around DNA.…”
Section: Dna In a Crowded Solutionmentioning
confidence: 99%